Study of clinico-pathological factors, indications and response to chemotherapy in breast cancer patients in a tertiary care hospital in south India - Shoeb, Mohammad Fazelul Rahman (International Surgery Journal, 2017)
Background: Breast cancer is considered a systemic disease, surgical interventions on most of the patients can reduce the loco regional burden and chemotherapy can reduce systemic burden by reducing chances of metastasis and recurrence and prolong life expectancy. The objective of this study was to assess the clinic-pathological factors of patient presenting with breast cancer and to study the indications and response to chemotherapy for breast cancer. Methods: A prospective study of fifty patients was carried out at Victoria hospital and Bowring and Lady Curzon Hospital between October 2010 to October 2012 who underwent surgery, chemotherapy, radiotherapy and hormonal therapy. Results: Most patients presented with palpable axillary lymph nodes (64%) and belonged to stage II disease (50%). Invasive ductal carcinoma was seen in 90% of cases while medullary in 04%, colloid in 2% and Infiltrating lobular was seen in 04% of patients. Totally 64% cases were ER or PR+, and 36% were ER/PR- among the study participants. 70% of the patients operated had positive nodes. All 50 cases received chemotherapy. Chemotherapy was indicated in node positive patients and in patients whose tumour was measuring more than 1 cm. After follow-up of 50 patients for about a period of two years, 3 patients died, 4 patients had metastasis and in the remaining 47 surviving patients none of them had recurrence at the end of second year. Conclusions: Most cases and belonged to Stage II disease with Invasive ductal carcinoma being most common histological subtype seen in 90% of cases. FNAC is good diagnostic procedure cost effective and reliable as all cases post-operative HPE confirmed malignancy. Patients should be treated by chemotherapy in indicated cases, as carcinoma breast is a systemic disease and chemotherapy can reduce systemic burden by reducing chances of metastasis and recurrence and prolong life expectancy.